Peningkatan Kemampuan Melatihkan Manajemen Stres Bagi Guru BK SMP di Kota Malang - Carolina Ligya Radjah; Nugraheni Warih Utami (Universitas Negeri Malang, 2024)
Abstract: Adolescents who experience difficulties in adjusting, consider their difficulties as pressure that can cause stress. Community service activities aim to improve the ability to train stress management for junior high school guidance and counseling teachers in Malang City. The service is carried out using training methods carried out for junior high school guidance and counseling teachers in Malang City. There were 40 training participants who were representatives of public and private junior high schools in Malang City. The results of the activities are formal training meetings and informal stress management training activities carried out on students. Community service activities in the form of increasing the ability to train stress management for junior high school guidance and counseling teachers in Malang City succeeded in providing understanding and ability for guidance and counseling teachers in helping students manage the stress experienced by students. Keywords: ; ; Abstrak Remaja yang mengalami kesulitan dalam menyesuaikan diri, menganggap kesulitannya sebagai tekanan yang dapat menimbulkan stress. Kegiatan pengabdian kepada masyarakat bertujuan untuk meingkatkan kemampuan melatihkan manajemen stress bagi guru BK SMP di Kota Malang. Pengabdian dilaksanakan dengan metode pelatihan yang dilaksanakan untuk guru BK SMP di Kota Malang. Peserta pelatihan berjumlah 40 orang yang merupakan perwakilan SMP Negeri dan Swasta di Kota Malang. Hasil kegiatan berupa kegiatan formal pertemuan pelatihan dan kegiatan informal pelatihan manajemen stress yang dilakukan pada siswa. Kegiatan pengabdian kepada masyarakat berupa peningkatan kemampuan melatihkan manajemen stress bagi guru BK SMP di Kota Malang berhasil memberikan pemahaman dan kemampuan guru BK dalam membantu siswa melakukan manajemen stress yang dialami siswa.